Novas aril-metil-piperazinas da série LINS01 como ligantes de receptores de histamina H3R/H4R - Nascimento, Lillian Ferreira Dos Santos [UNIFESP] (2019)
Histamine is an important biogenic amine distributed widely in all tissues. It plays an important role in the physiology and homeostasis of the organism, as well as in allergic and inflammatory processes. Its effects are observed through interaction with four histaminergic receptors G protein-coupled histaminergic receptors called H1, H2, H3 and H4, and the cell signaling that activates each receptor is distinct. The four histaminergic receptors are important targets for the treatment of various diseases. The first two receptors identified were already intensively researched and already have definite application in therapy. The H3 receptor has been characterized as auto and hetero-receptor and is found mostly in the central nervous system (CNS). It has thus become a promising target for the treatment of CNS disorders. Because it has been characterized later, the H4 receptor, present mainly in cells of hematopoietic origin, has been studied by several research groups as a target for the treatment of immunological and inflammatory diseases. Due to the homology between the H3 and H4 receptors many ligands may have affinity for both receptors. Thus, molecules with antagonistic or inverse agonist activity towards the H3 and/or H4 receptors demonstrate relevance in the treatment of several diseases involving alone or in combination these receptors. Therefore, the purpose of this work was to synthesize molecules based on the LINS 01 series with the highest yield and purity possible, to evaluate the affinity of these receptors for H3 and / or H4 receptors and to verify their activity as antagonist or agonist. Synthesis of the ligands involved steps such as allylation, Claisen rearrangement and reductive amination, resulting in intermediates which had crude yields of ~ 1 to 93%. The compounds designed in this work were not obtained due to the failure of chemical steps (low yield and / or no yield of the desired product) and purification. Thus, some intermediates obtained were tested through the binding test, but showed very low affinity in both receptors and thus it was not possible to evaluate their activities as antagonists or agonists in H3 and H4 receptors.